2020
DOI: 10.3389/fneur.2020.00725
|View full text |Cite
|
Sign up to set email alerts
|

Non-stenosing Carotid Atherosclerosis and Arterial Stiffness in Embolic Stroke of Undetermined Source

Abstract: Background and Purpose: Recent findings suggested that non-stenosing atherosclerosis (NSA) may play an important pathogenic role, especially in cryptogenic strokes. Furthermore, arterial stiffness has been suggested to be a useful tool in identifying patients with embolic stroke of undetermined source (ESUS) with poor neurological prognosis. In this view, the aim of our study was to assess the association between carotid NSA and arterial stiffness in ESUS patients, in order to better define the cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Third, aortic stiffness and wave reflection are associated with poor left ventricular conditions, which may increase the risk of poor outcomes 34 . Fourth, aortic stiffness is linked to atherosclerosis because both share several risk factors, including hypertension 35 . The current study showed that hypertension was common in 72.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Third, aortic stiffness and wave reflection are associated with poor left ventricular conditions, which may increase the risk of poor outcomes 34 . Fourth, aortic stiffness is linked to atherosclerosis because both share several risk factors, including hypertension 35 . The current study showed that hypertension was common in 72.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both ALDH2 and MRVI1 are involved in platelet adhesion [ 47 ] and vascular inflammation [ 48 , 49 ]. Previous research has linked increased blood-brain barrier permeability to an inflammatory process involving activated monocytes/macrophages in individuals with cerebral small vessel disease [ 50 , 51 ]. In our study, MRVI1 was more abundant in astrocytes, which supports their roles in vascular inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to physiological change from person to person the glucose level also altered among them and hyperglycemia can cause quick response to initiate macro complication. HbA1c is an accurate and precise measuring tool to diagnose chronic blood glucose levels and is more closely related to the complications risk than episodic or single glucose measurements [17]. Socioeconomic levels also considered as risk factor among the diabetes patients.…”
Section: Discussionmentioning
confidence: 99%